(3cJGH CSQGQ GdfSGAs - (3LGdjfhSs
(3ChdgG (B:s
(3SCdJ GdedcI LGdjfhS Cf jDda dgG cJGHkG ai CSQGQ GdfSGA Ydi eG SCdJg hHjfJ dg ZQVgG ai GdcJGH s
(3BNQgG (B:s
(3HCf jWQM dgG ai Ogf JfOgf Hg hgj dGJYde aEfg jaYd eG hUafG Je cJGH LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs